Cerminan Era Taisho pada Cerpen Yabu no Naka Karya Akutagawa Ryunosuke : Kajian New Historisicm - Ade Saikhu Sya'Ban; Antonius Rahmat Pujo Purnomo; Nadya Afdholy (IZUMI, 2026)
This article examines Akutagawa Ryūnosuke's short story Yabu no Naka (1922) as a critical reflection of the socio-political transformations during Japan's Taishō era (1912-1926). Using a New Historicism approach, the study reveals how the story's multiperspective narrative technique not only challenges the notion of absolute truth but also represents the paradoxes of Japan's modernization, including class tensions, gender dynamics, and legal authority. Through characters such as the woodcutter, the priest, the bandit Tajōmaru, and the samurai's wife Masago, Akutagawa portrays a society caught between traditional values and Western modernity. The article concludes that Yabu no Naka is a brilliant sociological portrait of truth's relativity and the complexities of social change in the Taishō era. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor